Inter-submodule unbalanced active power distribution of battery energy storage systems based on cascaded multilevel converters - Liang, Gaowen (Nanyang Technological University, 2022)
Operation and management of the power system are becoming increasingly challenging nowadays due to the rising number of renewable energy sources. Energy storage systems, especially battery energy storage systems (BESSs), are considered as an established solution to overcome the intermittency and fluctuation of the renewable power generation. Particularly, cascaded multilevel converters (CMCs) are suitable topologies to connect BESSs to the power system, where the batteries are integrated into the submodules (SMs). In the operation of the CMC-based BESSs, the preferred active power distribution among the SMs within one arm can be highly unbalanced due to various reasons, like balancing the state of charge (SoC) of the batteries, integrating different battery technologies into different SMs, etc. However, the preferred unbalanced inter-SM active power distribution may not be viable, which means that the SMs will fail to track their corresponding average active power (AAP) references correctly. This can result in harmful active power flows, like charging/discharging the SMs with excessive active power, over-charging/discharging the batteries in some SMs, etc. To overcome this challenge, this thesis develops a comprehensive analysis concerning the active power distribution among the SMs within one arm of the CMC-based BESSs. It is revealed that there exists maximum and minimum AAP that can be processed by a certain number of SMs, which determines the viability of the preferred inter-SM active power distribution. An analytical method is proposed to derive the SM AAP limits (AAPLs). Based on the derived SM AAPLs, an effective method is developed to determine the viability of the preferred active power distribution and how to modify the SM average active power references if the preferred distribution is unviable. Finally, this thesis develops a methodology to consider the SM average active power limits in the control of the BESS without compromising the control objectives. In particular, a constrained inter-SM SoC balancing algorithm is proposed, which can constrain the AAP of each SM within a safe and viable range during the SoC balancing. The proposed analysis and methods of this thesis not only apply to the CMC-based BESSs, but are also beneficial for the design and control of other applications where renewable energy sources and energy storages are integrated into the SMs of the CMCs.